PEMBUATAN GEL ANTINYERI DARI MINYAK ATSIRI BUNGA CENGKEH ( Syzygium aromaticum(L.) Merr.&Perry ) - Purgiyanti Purgiyanti; Rosaria Ika Pratiwi (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
Essential oils of clove flowers (Syzygium aromaticum (L.) Merr. Perry) are known to have properties as analgesic or painkillers. One of the efforts to utilize clove flower essential oil is to be used as an active ingredient in gel preparations. Gel preparations were chosen one of them is because it gives a cold effect on the skin when used on the skin. The material chosen for use as a gel base or gelling agent is CMC-Na. The use of CMC-Na as a base gel was varied with several different concentrations of the three formulas made, namely 3.5%, 5%, and 6.5%. Based on the results of the research analyzed in a theoretical approach by observing and comparing the results with several sources on organoleptic preparations, pH, clarity, dispersion, adhesion, and preference test obtained the best results in formula I with the use of CMC-Na gel base of 3, 5%. Keywords: Gel, Essential oil, Clove Flower, CMC-Na